(untitled) (Tikrit Journal For Political Science, 2024)
The accelerated developments in the world, cast their shadow on Iraq’s interactions with its regional neighborhood. In addition, the internal theme of political regimes and societal conditions is also reflected in the neutralization, change, or emergence of new regional variables effected on Iraq’s national security. Thus, it was found that these interactions alongside with national priorities lead to the necessity of adapting to new regional rules, whether in the form of threats or opportunities. This is what was assumed in this research, and verified through the use of multiple approaches, including the Analytical approache. It has been proven that Iraq needs a comprehensive national security strategy that supports and complements community plans, government programs, and economic development. This national strategy will facilitate and complement the Iraqi vision for the long term. In conclusion, one of the most important factors that work to neutralize the elements of the external threat to Iraqi national security is inherited in building internally agreed-upon Iraqi citizenship that enhances the spirit of belonging.